DRD4 polymorphism associated with greater positive affect in response to negative and neutral social stimuli. (16th May 2022) - Gilman, T. Lee; Ford, Matthew T.; Jasnow, Aaron M.; Coifman, Karin G.
Abstract : Abstract: Despite the robustness of DRD4 polymorphism associations with brain‐based behavioral characteristics in candidate gene research, investigations have minimally explored associations between these polymorphisms and emotional responses. In particular, the prevalent single nucleotide polymorphism (SNP) ‐521C/T (rs1800955) in the promoter region of DRD4 remains unexplored relative to emotions. Here, two independent samples were evaluated using different emotion elicitation tasks involving social stimuli: Study 1 ( N = 120) evoked positive and negative emotional responses to validated film clips; Study 2 ( N = 122) utilized Cyberball to simulate social rejection and acceptance. Across studies, C/C individuals self‐reported higher mean positive affect scores using Likert scales versus T carrier individuals, selectively when presented with neutral or negative (but not positive) social stimuli. The consistent findings across these two studies supports a functional consequence of this DRD4 SNP on emotion processing during changing social contexts. Continued investigation will help clarify if a C/C genotype enhances positive emotions under negative circumstances, or if the presence of the T allele reduces positive emotions, and how rs1800955 behavioral associations might generalize across different demographics. Future studies could also reveal if this SNP interacts with other changing environmental conditions to affect emotional responses, such as social limitations during the COVID‐19 pandemic.